Synthesis of redox-activated hollow mesoporous silica nanoparticles for efficient anti-cancer drug delivery - Teng, Siew Kee (2015)
In this study, hollow mesoporous silica nanoparticles were synthesized with redox-activated release for efficient delivery of anticancer drug specifically into cancer cells. A reaction between mercapto propyltrimethoxysilane (MPTS), which was grafted onto mesopores of HMSNs, and 2-carboxylethyl 2-pyridyl disulfide gives rise to a disulfide link, which is redox-cleavable in the presence of the reducing agent glutathione (GSH). Since amount of GSH is much higher in cancer cells than in normal cells, this gives tumor specificity and reduced side effects on normal cells. Furthermore, grafting of adamantanamine (Ada) followed by capping with β-CD allows for containment of the anticancer drug within the mesopores of HMSNs with minimal leakage until it has been delivered into the cancer cell itself. In-vitro studies show that DOX loaded HMSNs end-capped with β-CD has the highest drug delivery efficiency and can effectively cause cancer cell apoptosis, making this drug delivery system a potential carrier for future targeted cancer therapy. However, as small amounts GSH is initially present in normal cells, a small but insignificant amount of DOX could also be released to normal cells. Hence further research could be done to develop redox-activated HMSNs with greater specificity targeting chemicals or agents only found in cancer cells.